The Production of Crude Fish Oil from Trimming, Belly, and Head of Catfish (Pangasius pangasius) - Pangestika, Widya; Putri Salen, Sholekha Nur Karim; Setiawati, Natalia Prodiana; Arumsari, Kusuma; Maulid, Deden Yusman; Nusaibah, Nusaibah; Abrian, Satriya (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Fish oil is an extraction that comes from the tissue in fish which contains nutrients that are good for health. Catfish (Pangasius pangasius) is a type of fish that is widely cultivated in Indonesia. The oil content in catfish is quite a lot so it is suitable for use in making fish oil. Health supplements are products with the aim of maintaining, improving health as well in addition to the need for this substance. This research aims to determine the process of make fish oil, increasing the selling value of catfish as a health supplement. The test parameter in this research were to determine the free fatty acid, water content, and organoleptic content of fish oil. This research was conducted on three treatments with different types of raw materials, namely the body parts of catfish including belly, trimming and fish head. The most yield results are at fish oil with belly materials for catfish, is 35%. The water content and free fatty acids contained in fish oil in each treatment met the existing standards. From the results of observations of turbidity, color, and odor, it is known that fish oil obtained from the belly is better than fish oil from other parts.